2021
DOI: 10.1186/s40663-021-00334-8
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of microbial living communities and residues to soil organic carbon accumulation along a forest restoration gradient in southern China

Abstract: Background Forest restoration has been considered an effective method to increase soil organic carbon (SOC), whereas it remains unclear whether long-term forest restoration will continuously increase SOC. Such large uncertainties may be mainly due to the limited knowledge on how soil microorganisms will contribute to SOC accumulation over time. Methods We simultaneously documented SOC, total phospholipid fatty acids (PLFAs), and amino sugars (AS) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Vegetation restoration could enhance plant‐C inputs and in tandem stimulate soil microbial activities (Hu et al, 2020). Microbial products mainly accumulate in soils via microbial decomposition and turnover (Liang, 2020; Zhang et al, 2021). However, the contribution of GRSP and amino sugars to the SOC pool decreased along the afforestation chronosequence (Figure 3), suggesting an increase in the contribution of plant‐derived C to the SOC pool with forest restoration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vegetation restoration could enhance plant‐C inputs and in tandem stimulate soil microbial activities (Hu et al, 2020). Microbial products mainly accumulate in soils via microbial decomposition and turnover (Liang, 2020; Zhang et al, 2021). However, the contribution of GRSP and amino sugars to the SOC pool decreased along the afforestation chronosequence (Figure 3), suggesting an increase in the contribution of plant‐derived C to the SOC pool with forest restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is no consensus on the contribution of necromass to the SOC pool during vegetation restoration (Guo et al, 2021). A recent study showed that the concentrations of PLFAs and amino sugars respond differently to forest restoration in a subtropical region with divergent contributions of fungi or bacteria to the SOC pool via physical protection pathways (Zhang et al, 2021). Especially microbial communities and biomasses might vary with aggregate sizes due to their difference in microhabitats (Gupta & Germida, 2015), hence influencing the accumulation of amino sugars in soil aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that SOC storage is driven by soil physicochemical properties (pH, moisture, total N, total P, available C, available N, and available P), microbes (fungal and bacterial decomposition groups), and plants (plant community and plant litter quality). Among the dozens of biotic and abiotic factors affecting SOC storage (Averill et al, 2014;Wu et al, 2017;Luo et al, 2020;Chen et al, 2021;Wang et al, 2021;Zhang et al, 2021), soil properties have received much attention. For example, N limits C storage in terrestrial ecosystems, even in N-rich tropical forests (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In forest ecosystems, land-use changes resulting from natural vegetation restoration can significantly alter carbon storage and fixation (Zhang and Shangguan, 2016). Forest restoration influences the equilibrium between the carbon input and output processes from plant and microbial sources by altering the soil carbon pool (Jastrow et al, 2007;Zhang et al, 2021). According to Erskine et al (2006), trees can add carbon to the soil, and this process can be affected by the tree species and the external environment.…”
Section: Introductionmentioning
confidence: 99%